Use of a Ca-selective electrode in the determination of total Ca in the production of crude sugar - González García, Jorge; Egonov, V. V.; Del Tóro Dénis, Rubén; Del Tóro Dénis, E.; Martinéz Sáez, Silvio; Ramos Vega, A. (Eclética Química, 1997)
The determination of the total calcium in juice, syrups, and other products of the sugar industry is investigated. Total calcium and free calcium is determinated by AAS and employing Ca-selective electrode respectively. A coefficient is obtained for the relation of total calcium with respect to free calcium. The coefficient is employed to determine the content of total calcium in accordance with the following equation. Relative error is less than 5 %.